PERBANDINGAN PENGAPLIKASIAN FOUNDATION DENGAN SPATULA KOREAN DAN BEAUTY BLENDER TERHADAP KUALITAS HASIL TATA RIAS WAJAH SEHARI-HARI - Sabrina Halimatus Sakdiyah; Dindy Sinta Megasari; Maspiyah; Octaverina Kecvara Pritasari (Jurnal Tata Rias, 2025)
Cosmetics have been known for centuries where humans want to look beautiful and attractive. Cosmetics developed in Europa and Asia. South Korea is country with a very rapid development of the beauty world, the korean look trend has techniques, one of which is applying foundation with a korean spatula and applying foundation with a beauty blender which is a common choice of makeup artists around the world. The purpose of this study was to determine the final result and comparison of application with a korean spatula and beauty blender including aspects of coverage, smoothness, and durability. this study used quantitative with quasi exsperimental research design. the results proved that: (1) the coverage aspect of the korean spatula 3,1 gives a smooth and even effect but is not effective enough in covering blemishes and spots. the covverage aspect with the beauty blender 3,7 because it produces an even appearance and effectively covers blemishes and imperfections. (2) the smoothness aspect of the 3.7 korean spatula creates a fairlly even appearance because when applying it can reach widely and thinly which makes the foundation not lumpy while the 3.5 beauty blender is not better because the shape has quite a lot of pores making the smoothness results not smooth enough and the range is limited. (3) the durability aspect of the 3.3 korean spatula can last 3 hours because this technique of application on facial skin does not reach the pores while the beauty blender can last more thean 3 hours. Keywords: korean spatula, beauty blender, daily makeup.